2018
DOI: 10.3892/ijo.2018.4648
|View full text |Cite
|
Sign up to set email alerts
|

OxLDL promotes lymphangiogenesis and lymphatic metastasis in gastric cancer by upregulating VEGF‑C expression and secretion

Abstract: Gastric cancer is one of the most malignant tumor types, and its metastasis is a notable cause of mortality. Among the methods of tumor metastasis, lymphatic metastasis is the predominant one in gastric cancer. A previous study reported that the plasma oxidized low-density lipoprotein (oxLDL) is the risk factor associated with the development of tumors in patients with abnormal lipid metabolism, but the influence of plasma oxLDL in the lymphatic metastasis of gastric cancer remains unclear. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
(73 reference statements)
1
28
0
Order By: Relevance
“…Overexpression of LOX-1 has also been observed in several other metabolic diseases including endothelial dysfunction, atherosclerosis and obesity (55,56). In these disorders, These findings were also confirmed by clinical data demonstrating that plasma oxLDL levels positively correlated with lymphatic metastasis in patients with gastric cancer (60).…”
Section: Oxldl and Carcinogenesissupporting
confidence: 65%
“…Overexpression of LOX-1 has also been observed in several other metabolic diseases including endothelial dysfunction, atherosclerosis and obesity (55,56). In these disorders, These findings were also confirmed by clinical data demonstrating that plasma oxLDL levels positively correlated with lymphatic metastasis in patients with gastric cancer (60).…”
Section: Oxldl and Carcinogenesissupporting
confidence: 65%
“…As the P value of FAM3D in TCGA was close to 0.05 and no studies have shown that FAM3D is associated with GC, the relationship between FAM3D and GC was worthy of further study. Studies have shown that OLR1 is positively correlated with lymph node metastasis of GC 34 .…”
Section: Discussionmentioning
confidence: 97%
“…VEGFC has been reported to be a key regulator in GC progression and its encoded protein facilitates angiogenesis and endothelial cell growth. In addition, oxidised low-density lipoprotein (oxLDL) is a risk factor in the pathogenesis of cancers linked to its roles in abnormal lipid metabolism, and has been shown to promote lymphatic metastasis of GC via the up-regulated expression and secretion of VEGFC [ 15 ]. microRNA (miR)-27b acts as a potential tumour suppressor in GC and targets VEGFC expression [ 16 ], while miR-101 promotes cisplatin (DPP)-induced apoptosis partly via its targeting of VEGFC in DDP-resistant GC cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%